Challenges, target and strategies for sustainable wheat production for food security and nutrition - Sharma, Indu; Chatrath, Ravish; Sendhil, R (Indian Farming, 2015)
Despite India achieving the selfsufficiency status in wheat production and enhancing its potential to manage the inter year fluctuations in production, the problem of household food security and nutrition security is still a puzzle. The country’s wheat breeding programme is expected to face an impending crisis with respect to future wheat demand. In view of the trans-challenges, increasing the crop productivity is a possible solution to address the issue on food and nutrition security. Incremental yield could be achieved through concerted research and its benefit (access to wheat) should have an out reach via synergy between research, developmental and extension programmes. An integrated mission mode research and development in all the crops will lay a basis for building the nation towards food and nutritional security.